INTEGRATED COURSE MANAGEMENT TO IMPROVE THE SPECIFIC SKILLS OF PROFESSIONAL BARISTAS - Pujiono, Sugeng; Rostini, Deti; Hendra, Agus (Jurnal Konseling Pendidikan Islam, 2025)
The coffee industry in Indonesia has experienced rapid growth, leading to an increasing demand for professional baristas with specific skills such as espresso extraction, latte art, and manual brewing techniques. However, available barista training programs are not yet fully integrated with the needs of the industry. This study aims to analyze integrated course management in enhancing the specific skills of professional baristas at two training institutions, namely LKP Sugeng Sejahtera (West Bandung Regency) and LKP Karya Duta (Bandung City). This research uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The findings show that both institutions implement training management based on G.R. Terry's theory, which includes planning, organizing, actuating, and controlling. These are complemented by industry-adjusted curricula, involvement of business partners, and competency-based evaluations. The challenges encountered include limited facilities, gaps in instructor competencies, and the suboptimal sustainability of post-training programs. Solutions are pursued through strengthening industry partnerships, updating curricula, and continuous evaluation. It can be concluded that integrated course management plays a vital role in bridging skill gaps and enhancing barista professionalism, and it is relevant as a model for the development of other vocational training programs.